Una mirada al panorama socioeconómico, ambiental y fiscal de la minería del carbón en el Cesar (2014)
This article carries out a review on social and environmental transformation that has happened in the department of Cesar, because of the setting up and fast growth of the surface coal mining since the decade of the nineties. Considering the concept of Enclave Economy, the statistic information is taken to demonstrate that the coal mining in the Colombian department of Cesar adjust to that pattern with its social an economic consequences, along with de environmental damage inherent to this type of activity. The observed result is a deep transformation on the economic structure of that department which, besides the greater public incomes -as royalties- that mining generates, it brings out several questions, not just on State revenues, but also about environment, welfare, economic development and regional productive options.